Perception management in the art of war - Huhtinen, Aki-Mauri; Rantapelkonen, Jari (Tiede ja ase, 2002)
"Perception management is integral to the art of war. Skilful use of information warfare, psychological operations and propaganda is problematic, however. Based on Maurice Merleau-Ponty’s theory of perception and the practical examples presented in this artic1e - the Finnish Winter War and the war on terrorism - it can be held that perception and its interpretation can never be certain.1f perceptions are manufactured, they can become counter-productive. The way in which perceptions arise is characterised by dynamism. According to Merleau-Ponty, there is always a middle ground between us and the enemy, a field that distorts and limits our view of the enemy. Therefore, in this artic1e we propose that we can direct propaganda only towards ourselves."